THE ROLE OF DIGITAL DICTIONARY OF TRANSLATOR AR-ID IN MODERN ARABIC ERA SOCIETY 5.0 - Baiq Wahyu Diniyati Hidayatillah; Muallifah Muallifah; Nur Hasaniyah (Faculty of Humanities UIN Maulana Malik Ibrahim Malang, 2024)
The all-digital era of society 5.0 is considered a concept of society, centered on humans and based on technology. Progress in these various fields has given rise to many new vocabularies, of course a dictionary is needed to know and understand the meaning properly and correctly. Thus, the dictionary has a very important role in learning, especially the Arabic dictionary. Advances in technology, dictionaries are no longer in the form of sheets of paper, but are already in digital form which can be accessed with various media in the form of smartphones, laptops, tablets and so on. The purpose of this study is to reveal how the sources of the formation of modern Arabic and how the role of Translator AR-ID in interpreting new terms of modern Arabic in the era of society 5.0. This type of research is descriptive research using the Literature study. The results of this study reveal the sources of the formation of Modern Arabic consisting of Arabicization, Derivation, Arabicization and Derivation Preferences, Merger. One of the modern tools that can help translate Indonesian-Arabic is to use digital applications; digital dictionaries have an important role in translating new terms and vocabulary in modern Arabic. Because the digital dictionary always gets the latest updates regarding new words and meanings in every language, especially modern Arabic